(untitled) (Research, Society and Development, 2022)
The knowledge acquired during the undergraduate nutrition course can impact the eating behavior and perception of the body image of its students, so the objective of the research was to evaluate the nutritional status, eating attitudes and identify their body perception in undergraduates of the course. of nutrition, being a descriptive, transversal, epidemiological-nutritional and behavioral research, with data collection from a form containing socioeconomic data, Food Attitudes Scale (EAAT) and Silhouette Scale. Statistical analysis was performed using the SPSS online version, considering p<0.05. A total of 83 university students aged between 21 and 23 years old participated in the research, being 97.6% single and 83% without associated work activity. Eutrophy prevailed in 67.5% regardless of the semester of the course, however, overweight was more prevalent in students in the intermediate semesters 31.8% and 29.7% in the final semesters, and obesity in the initial semesters 4.1%. As for their body weight, 40.8% were dissatisfied. The students from the initial and intermediate semesters presented disordered eating with an EAAT score higher than the general average (67.7) and all the subscales analyzed were altered. Weight and body image were a concern present in nutrition students, indicating a desire to adapt to the standards established by society, associated with a dysfunctional diet.